2019
DOI: 10.1016/j.petrol.2019.106388
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of methane hydrate nucleation and growth by an antifreeze protein

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Therefore, the trends observed for the average T on for fresh and memory solutions at 30 and 36 bar are: [C 2 OHth][Br] < [C 2 th][Br] ≈ Milli-Q water and [C 2 th][Br] ≈ Milli-Q water < [C 2 OHth][Br], respectively. Similar behavior of hydrate nucleation in the presence of additives has been reported elsewhere [ 57 , 61 ].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, the trends observed for the average T on for fresh and memory solutions at 30 and 36 bar are: [C 2 OHth][Br] < [C 2 th][Br] ≈ Milli-Q water and [C 2 th][Br] ≈ Milli-Q water < [C 2 OHth][Br], respectively. Similar behavior of hydrate nucleation in the presence of additives has been reported elsewhere [ 57 , 61 ].…”
Section: Resultssupporting
confidence: 86%
“…The constant ramping method is a well-perceived method in the literature [ 56 , 57 ] which has been used to obtain the nucleation onset temperatures to screen the efficiency of given kinetic hydrate inhibitors at low concentrations. The results of the nucleation (T on ) onset temperatures of CO 2 hydrates in solutions of 1 wt% ILs and Milli-Q water at two different pressures are given in Table 2 along with the standard deviations and plotted in Figure 4 (left).…”
Section: Resultsmentioning
confidence: 99%
“…A phenomenon recognized by many researchers as the water "memory effect", however, may cause natural gas hydrates to form easier after being dissociated or melted down [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. In these studies, the memory effect is observed as a shorter induction time during a constant subcooling or as a smaller subcooling phase during a linear cooling ramp.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, insect AFPs exhibit TH up to 5 °C and are, thus, classified as hyperactive. , Tenebrio molitor ( Tm )­AFP, a biodegradable substance, has a high TH, which makes it an excellent ice-growth inhibitor. Although AFPs effectively inhibit hydrate growth, the precise mechanism through which this occurs requires further investigation. Therefore, in this study, molecular dynamics (MD) simulations were employed to investigate the mechanism of the hyperactive insect antifreeze protein Tm AFP in inhibiting methane hydrate growth.…”
Section: Introductionmentioning
confidence: 99%